2020
DOI: 10.3390/f11090909
|View full text |Cite
|
Sign up to set email alerts
|

Prototyping a Geospatial Atlas for Wildfire Planning and Management

Abstract: Wildland fire managers are increasingly embracing risk management principles by being more anticipatory, proactive, and “engaging the fire before it starts”. This entails investing in pre-season, cross-boundary, strategic fire response planning with partners and stakeholders to build a shared understanding of wildfire risks and management opportunities. A key innovation in planning is the development of potential operational delineations (PODs), i.e., spatial management units whose boundaries are relevant to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 64 publications
(91 reference statements)
0
14
0
Order By: Relevance
“…Travel rates used in geospatial modeling can simulate the evacuation of a fire crew in comparison to predicted fire behavior in order to assess potential trigger points on the landscape that a fire crew could use [51]. Beyond SZs and escape routes, there is an emergence of other geospatially driven approaches for fire management that have implications for firefighter safety, such as the mapping of snag hazards [52], the spatially explicit estimation of suppression difficulty [2,53], the prediction of potential control locations [3,54], and the mapping of potential wildland fire operational delineations [55,56]. These tools are now commonly used in the US to enhance situational awareness and improve the quality of strategic decision-making on large and complex wildfire incidents [57].…”
Section: Discussionmentioning
confidence: 99%
“…Travel rates used in geospatial modeling can simulate the evacuation of a fire crew in comparison to predicted fire behavior in order to assess potential trigger points on the landscape that a fire crew could use [51]. Beyond SZs and escape routes, there is an emergence of other geospatially driven approaches for fire management that have implications for firefighter safety, such as the mapping of snag hazards [52], the spatially explicit estimation of suppression difficulty [2,53], the prediction of potential control locations [3,54], and the mapping of potential wildland fire operational delineations [55,56]. These tools are now commonly used in the US to enhance situational awareness and improve the quality of strategic decision-making on large and complex wildfire incidents [57].…”
Section: Discussionmentioning
confidence: 99%
“…When combined with local experiential knowledge, spatially explicit decision support tools like quantitative risk assessments 63 , suppression difficulty maps 64 , and potential control location atlases provide stakeholders with a common operating picture that can be used as the basis for co-managing risk 30 , 65 . Mapping the components of fire risk allows all landowners to simultaneously assess their exposure to wildfire and their contribution to the exposure of adjoining jurisdictions 66 , 67 . Transparency in pre-fire planning and risk governance can help build consensus around which actors are responsible for managing specific components of CB fire risk.…”
Section: Discussionmentioning
confidence: 99%
“…Many of those would likely allow us to improve future program, regional and national fire program budgeting analysis. For example, a recent study from Thompson et al (2021) suggested preseason and strategic fire planning following potential operational delineations (PODs), which are spatial management units with boundaries relevant to fire containment operations features such as roads, ridgetops, and fuel transitions. Fire risk attributes such as fire consequences, suppression opportunities, and strategic response objectives can be analyzed for each POD to optimize fire management decision making within them.…”
Section: Discussionmentioning
confidence: 99%